O Pewnym Stochastycznym Modelu dla Problemu Uderzenia - Kumarswamy, S.; Subramanian, R. (Engineering Transactions, 1971)
This paper is a study of the response of plates subjected to projectile impacts. The impact is represented by a velocity assumed to be random. The material response is taken to be of Voight type. Expressions for the estimates (in the form of expectations) of displacement and stress are derived.